Qualitative factors as determinants of continued success: An examination of eBusiness entrepreneurial firms using the New Venture Template - Ervin L. Black; F. Greg Burton; Peter M. Johnson (The Journal of Entrepreneurial Finance and Business Ventures, 2009)
In this study, we analyze eBusiness entrepreneurs nominated by the Ernst & Young Entrepreneur of the Year Award program to ascertain whether qualitative factors are correlated with success. We find qualitative factors are incrementally informative above and beyond the information provided by quantitative factors. More specifically, firms that are able to maintain their innovative strategies by improving upon the product (or service) they offer and are able to meet the long-term needs of the customer are more likely to experience increased sales growth and have greater access to capital which results in a successful harvest strategy.
Keywords: 650